Role of endothelial microRNA 155 on capillary leakage in systemic inflammation - Etzrodt, Valerie; Idowu, Temitayo O.; Schenk, Heiko; Seeliger, Benjamin; Prasse, Antje; Thamm, Kristina; Pape, Thorben; Müller-Deile, Janina; van Meurs, Matijs; Thum, Thomas; Garg, Ankita; Geffers, Robert; et al. (Critical Care, 2021)
Background: Capillary leakage is a key contributor to the pathological host response to infections. The underlying mechanisms remain incompletely understood, and the role of microRNAs (MIR) has not been investigated in detail. We hypothesized that specific MIRs might be regulated directly in the endothelium thereby contributing to vascular leakage. Methods: SmallRNA sequencing of endotoxemic murine pulmonary endothelial cells (ECs) was done to detect regulated vascular MIRs. In vivo models: transgenic zebrafish (flk1:mCherry/l-fabp:eGFP-DPB), knockout/wildtype mouse (B6.Cg-Mir155tm1.1Rsky/J); disease models: LPS 17.5 mg/kgBW and cecal ligation and puncture (CLP); in vitro models: stimulated human umbilical vein EC (HUVECs), transendothelial electrical resistance. Results: Endothelial MIR155 was identified as a promising candidate in endotoxemic murine pulmonary ECs (25 × upregulation). Experimental overexpression in a transgenic zebrafish line and in HUVECs was sufficient to induce spontaneous vascular leakage. To the contrary, genetic MIR155 reduction protects against permeability both in vitro and in endotoxemia in vivo in MIR155 heterozygote knockout mice thereby improving survival by 40%. A tight junction protein, Claudin-1, was down-regulated both in endotoxemia and by experimental MIR155 overexpression. Translationally, MIR155 was detectable at high levels in bronchoalveolar fluid of patients with ARDS compared to healthy human subjects. Conclusions: We found that MIR155 is upregulated in the endothelium in mouse and men as part of a systemic inflammatory response and might contribute to the pathophysiology of vascular leakage in a Claudin-1-dependent manner. Future studies have to clarify whether MIR155 could be a potential therapeutic target. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05
Keywords: Endothelium; MicroRNAs; Respiratory distress syndrome; Sepsis; Tight junctions